Elaboración del plan de gerencia del diseño, compras, montaje, comisionamiento y puesta en marcha del sistema de control de la planta de generación eléctrica de la estación EL PORVENIR (2015)
The Degree Work consists of the preparation of a Management Plan for the design, procurement, assembly, commissioning and commissioning of the control system of the power generation plant of El Porvenir Station with subordinated stakeholder management plans, scope , time, cost and quality to be implemented by SIEMENS SA in projects of the same type, which will serve as a guide for the Project Managers of SIEMENS SA, in the development of future projects and in this way, help to have successful projects. The project object of this management plan, is born from the market conditions, the increase of the crude production and the need to increase the transport capacity towards the refining and export points, therefore OCENSA S.A. establishes a plan to become Colombia's most efficient oil pipeline transport platform. As part of this strategic plan, the Power Capacity Expansion Project 135 (P135) was created, which includes the engineering, supply, construction, assembly, commissioning, operation and maintenance of the electric power generation system for the El Porvenir station, through the which is intended to increase the transport capacity by 135,000 barrels per day.